Pengaruh Sudut Baca dan E-Book Terhadap Minat Baca Serta Kemampuan Membaca Intensif pada Siswa Kelas V Sekolah Dasar di Kecamatan Kemayoran - Nurhaeni, Heni; Suparti, Suparti; Syafruddin , Syafruddin (Riviera Publishing, 2025)
The development of reading interest and intensive reading ability of students in elementary schools is one of the important values that must be developed. Through the government program, there is a requirement for every school to have a reading corner and e-books provided to improve student literacy. The purpose of this study is to determine the effect of reading corners on the interests of fifth grade students in elementary schools. To determine the effect of reading corners on the intensive reading ability of fifth grade students in elementary schools. To determine the effect of Ebooks on the interests of fifth grade students in elementary schools. To determine the effect of Ebooks on the intensive reading ability of fifth grade students in elementary schools. To determine the effect of reading corners and ebooks together on the interests of fifth grade students in elementary schools. To determine the effect of reading corners and ebooks together on the intensive reading ability of fifth grade students in elementary schools. This study was conducted on elementary school students in Kemayoran District with a population of 3962. The sample used in this study was 363 students. Variable measurement using a Likert scale questionnaire and intensive reading ability test. Data analysis using simple regression to determine the effect of each independent variable on the dependent variable. There is a significant influence between the reading corner variable on students' reading interest) in elementary schools throughout Kemayoran District, which is 0.508 or 50.8%. There is a significant influence between the reading corner variable on students' intensive reading ability in elementary schools throughout Kemayoran District, which is 0.029 or 2.9%. E-books have a significant effect on students' interest from the results of the study obtained p-value <0.001. E-books have an effect on students' intensive reading ability obtained from the p-value <0.034. Reading corners and e-books together have an effect on students' interest seen from the p-value 0.000 <0.05. Reading corners and e-books together have an effect on students' reading ability because the p-value 0.005 <0.05.